The foundations of financial inclusion: Understanding ownership and use of formal accounts - Allen, Franklin; Demirguc-Kunt, Asli; Klapper, Leora; Martinez Peria, Maria Soledad (Journal of Financial Intermediation, 2016)
Financial inclusion—defined as the use of formal accounts—can bring many benefits to individuals. Yet, we know very little about the factors underpinning it. This paper explores the individual and country characteristics associated with financial inclusion and the policies that are effective among those most likely to be excluded: poor, rural, female or young individuals. Overall, we find that greater financial inclusion is associated with lower account costs, greater proximity to financial intermediaries, stronger legal rights, and more politically stable environments. However, the effectiveness of policies to promote inclusion varies depending on the characteristics of the individuals considered.